1. Substitute \( a = -8 \) and \( b = -6 \) into the expression:
\frac{5(-8)}{10(-6)} - 10(-6)^2 + 8
2. Simplify \( \frac{5(-8)}{10(-6)} \) :
\frac{5 \times (-8)}{10 \times (-6)} = \frac{-40}{-60} = \frac{2}{3}
3. Calculate \( 10(-6)^2 \) :
10 \times (-6)^2 = 10 \times 36 = 360
4. Substitute these values back into the expression:
\frac{2}{3} - 360 + 8
5. Combine the terms carefully:
\frac{2}{3} + 8 = \frac{2}{3} + \frac{24}{3} = \frac{26}{3}
6. Subtract 360:
\frac{26}{3} - 360 = \frac{26}{3} - \frac{1080}{3} = \frac{26 - 1080}{3} = \frac{-1054}{3}
7. Final result is:
\frac{-1054}{3}
The answer is \(-\frac{1054}{3}\).